PENGEMBANGAN SISTEM INFORMASI LABORATORIUM BERBASIS WEB DI LABORATORIUM PENDIDIKAN FSRD ISI SURAKARTA - Ahmad Kafidhi Sayuti (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
This research aims to produce a laboratory information system at the Laboratory of the Faculty of Fine Arts and Design of the Indonesian Art Institute of Surakarta. The research method used is developmental research using the SDLC (System Development Life Cycle) development methodology, the waterfall model with its stages is requirement (identification of needs), analysis, design, implementation and testing. The system produced is web-based application using the PHP and MySQL programming languages. This information system can be used to process laboratory equipment data starting from an inventory of equipments, materials, use, checking, returning, making reports and other documentation. All these services will use the application program, so that the processing time will be faster with minimal error rates. This system can display a report on the number of equipment usage statistics, the number of the top ten equipments that are often borrowed, reports of good or damaged equipment conditions and reports of equipment usage records. The model design of this system is illustrated by the Data Flow Diagram (DAD) model. Control design is focused on the security of accessing pages, data and information available by determining three levels of users, namely admin, operator and user.